The organosolv fractionation of cork components - Cordeiro, N.; Neto, C. P.; Rocha, J.; Belgacem, M. N.; Gandini, A. (HOLZFORSCHUNG, 2002)
Extractive-free cork from Quercus suber L. was submitted to organosolv fractionation and the effects of different process variables, such as ethanol/water ratio, temperature, time and the presence of acidic or alkaline catalysts, were studied. The variation of the relative proportions of extracted components, as a function of the processing conditions, could thus be established. Whereas the addition of 0.1 M acetic acid only increased the yield of extracted materials from about 15 to 23 %, the use of sodium hydroxide, at the same concentration, produced a jump to 76 %. In the case of the alkaline organosolv fractionation. an increase in process temperature, time and catalyst concentration led to an increase in the extraction yield, although in some cases this increase did not follow a sustained trend, as in the case of reaction time. Increasing the ethanol/water ratio led to a higher selectivity in favour of suberin extraction. Residual cork from different organosolv processes was characterised by FTIR and C-13 solid-state NMR. The latter technique provided some valuable information about both process selectivity and cork morphology, particularly with respect to the positioning of suberin macromolecules in the cell wall.
The following values have no corresponding Zotero field: pub-location: GENTHINER STRASSE 13, D-10785 BERLIN, GERMANY publisher: WALTER DE GRUYTER & CO
Keywords: C-13 NMR; Cork; ethanol/water extraction; FTIR; organosolv fractionation; Quercus Suber L; suberin

Cork suberin as an additive in offset lithographic printing inks - Cordeiro, N.; Blayo, A.; Belgacem, N. M.; Gandini, A.; Pascoal Neto, C.; LeNest, J.-F. (Industrial Crops and Products, 2000)
Suberin oligomers, isolated from cork (Quercus suber L.), were used as additives in ‘Waterless’ and vegetable-oil ink formulations, in the range of 2–10% w:w. The rheological behaviour of the suberin oligomers as well as of the inks, with and without suberin, were investigated as a function of temperature. It was shown that the addition of suberin induces a decrease of viscosity of both inks. The tack of pristine inks, suberin oligomers and their mixtures were determined at different temperatures: the variation of this parameter as a function of time provided information about the drying kinetics of these formulations. The tack of the ‘Waterless’ ink was found to increase with the introduction of suberin, whereas that of vegetable-oil based counterparts decreased. All the trends observed were interpreted in terms of the differences in composition between the two types of inks. Preliminary printing tests were carried out with the various suberin-containing inks
Keywords: Additive; Quercus suber L.; rheological properties; suberin; Tack; Vegetable oil-based ink; Viscosity; Waterless ink

Urethanes and polyurethanes from suberin 2: synthesis and characterization - Cordeiro, N.; Belgacem, M. N.; Gandini, A.; Neto, C. P. (INDUSTRIAL CROPS AND PRODUCTS, 1999)
Polyurethanes based on suberin from cork of Quercus suber L. and conventional isocyanate monomers were prepared and fully characterized in terms of both structure (FTIR and H-1 NMR spectroscopy) and thermal properties (differential scanning calorimetry and thermogravimetric analysis). Two fractions were systematically isolated, namely (i) methylene-chloride soluble products, which corresponded to linear and branched macromolecules and (ii) methylene-chloride insoluble products, representing the crosslinked material. The structures of these polymers were regular and no appreciable side reactions were detected. DSC analyses provided information about the glass transition temperature of both fractions and this parameter was correlated with the stiffness of the isocyanate used. The TGA of these polyurethanes showed that they started to degrade at about 175 degrees C and that the residue at 400 degrees C was around 50%. The highest amounts of insoluble fractions, as well as the highest T-g,s, were reached when an initial \{[\}NCO]/\{[\}OH] of unity was used. (C) 1999 Elsevier Science B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: Cork; glass transition; polyurethanes; Quercus suber L.; suberin; thermal properties

Cork suberin as a new source of chemicals. 1. Isolation and chemical characterization of its composition. - Cordeiro, N.; Belgacem, M. N.; Silvestre, a J.; Pascoal Neto, C.; Gandini, A. (International journal of biological macromolecules, 1998)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1H- and 13C-NMR, gas chromatography coupled with mass spectrometric (GC-MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be omega-hydroxymonocarboxylates, alpha, omega-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.
The following values have no corresponding Zotero field: accession-num: 9585884
Keywords: Alkaline methanolysis; Chemical characterization; Cork; Molecular weight distribution; Quercus suber L.; suberin

Cork suberin as a new source of chemicals: 2. Crystallinity, thermal and rheological properties - Cordeiro, N.; Belgacem, N. M.; Gandini, A.; Neto, C. P. (Bioresource technology, 1998)
Suberin samples, obtained by alkaline methanolysis from cork (Quercus suber L.), were submitted to various physical characterizations; DSC, TGA, optical microscopy, density and rheological properties. A sub- stantial proportion of these oligomers possessed a microcrystalline character with a melting range between 0 and 50°C. The amorphous part was liquid at room temperature and did not display a detectable glass transition upon cooling because of its wide molecular weight distribution. The viscous behaviour of suberin at room temperature was both plastic and thixotropic because of the structuring role of the micro- crystals
Keywords: Alkaline methanolysis; cork of Quercus suber L.; crystallinity; Density; rheological properties; suberin; thermal characterization

13C solid-state nuclear magnetic resonance and Fourier transform infrared studies of the thermal decomposition of cork. - Pascoal Neto, C.; Rocha, J.; Gil, A.; Cordeiro, N.; Esculcas, a P.; Rocha, S.; Delgadillo, I.; de Jesus, J. D.; Correia, a J. (Solid state nuclear magnetic resonance, 1995)
The thermal decomposition of cork has been studied by Fourier transform infrared (FTIR) spectroscopy and 13C solid-state nuclear magnetic resonance (NMR) spectroscopy with cross-polarization and magic-angle spinning (CP-MAS), high-power 1H decoupling (HPDEC) and cross-polarization depolarization-polarization (CPDP). Waxes and other soluble components of cork begin to decompose at ca. 150 degrees C. This is accompanied by partial decomposition of suberin, probably initiated at the points of attachment to the cell wall. The carbohydrates begin to decompose at ca. 200 degrees C. The decomposition of lignin begins at 250-300 degrees C, while suberin undergoes further degradation. Significant amounts of coke are formed in the process. At 400 degrees C cork has been transformed into coke with traces of partially decomposed suberin. The thermal decomposition of cork is dependent on the calcination time, particularly in the 200-350 degrees C range.
The following values have no corresponding Zotero field: accession-num: 7773647
Keywords: Fourier Transform Infrared (citation); Hot Temperature; Lignin; Lignin: chemistry; Lipids; Magnetic Resonance Spectroscopy; Membrane Lipids; Membrane Lipids: chemistry; Polysaccharides; Polysaccharides: chemistry; Spectroscopy

Characterization of the cork surface by inverse gas chromatography - Cordeiro, N.; Neto, C. P.; Gandini, A.; Naceur Belgacem, M. (Journal of colloid and interface science, 1995)
Inverse gas chromatography (IGC) at infinite dilution has been used to study the surface properties of cork from Quercus suber. The dispersive component of its surface energy was determined at different temperatures using n-alkanes as probes, and a GDS value of 38+-1mJ.m-2 at 40ºC was obtained. The surface acid (A)/base(B) properties were also evaluated by using polar probes and the results indicate that cork has an amphoteric character, with a KA/KB=1.1. The advantages of IGC, compared with the technique of contact angle measurements in the characterization of the cork surface, are discussed
Keywords: Cork; Inverse Gas Chromatography (IGC); surface properties (PG)